2014
DOI: 10.1016/j.mgene.2013.12.005
|View full text |Cite
|
Sign up to set email alerts
|

The great diversity of major histocompatibility complex class II genes in Philippine native cattle

Abstract: Bovine leukocyte antigens (BoLA) are extensively used as markers for bovine disease and immunological traits. However, none of the BoLA genes in Southeast Asian breeds have been characterized by polymerase chain reaction (PCR)-sequence-based typing (SBT). Therefore, we sequenced exon 2 of the BoLA class II DRB3 gene from 1120 individual cows belonging to the Holstein, Sahiwal, Simbrah, Jersey, Brahman, and Philippine native breeds using PCR-SBT. Several cross-breeds were also examined. BoLA-DRB3 PCR-SBT identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
43
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 36 publications
7
43
1
1
Order By: Relevance
“…Those same alleles were also detected in the Hereford × Jersey crossbreed at high frequencies (12.0% and 14.8%, respectively) (Table ). DRB3*4501 was rarely detected in other groups in this and other studies . Figure A also shows that Hereford was characterized by a low PC2 value, which was strongly influenced by the frequencies of BoLA‐DRB3*1601 and DRB3*3202 .…”
Section: Resultssupporting
confidence: 55%
“…Those same alleles were also detected in the Hereford × Jersey crossbreed at high frequencies (12.0% and 14.8%, respectively) (Table ). DRB3*4501 was rarely detected in other groups in this and other studies . Figure A also shows that Hereford was characterized by a low PC2 value, which was strongly influenced by the frequencies of BoLA‐DRB3*1601 and DRB3*3202 .…”
Section: Resultssupporting
confidence: 55%
“…; Takeshima et al . ). In Holstein × Jersey animals (0–50% Holstein) five alleles reached >5% frequency ( DRB3*0101, *1101, *1201, *1501 and *2703 ), and the same alleles had high frequencies in the 75–100% Holstein group as well (Table ).…”
Section: Discussionmentioning
confidence: 97%
“…It is worth noting that a review of the IPD-MHC database showed that some variants had been previously detected in other Asian breeds (BoLA-DRB3*031:03, *058:01 and *064:02 in Chinese yellow cattle , BoLA-DRB3*013:03 in Korean Hanwoo cattle and BoLA-DRB3*049:01 in the Indian Red Sindhi); African Zebu breeds (BoLA-DRB3*038:01 in Ethiopian Arsi and BoLA-DRB3*013:03 in Sudanese Baggara) and other Asian Bos species, including BoLA-DRB3*013:03 in Indonesian Bos javanicus . In previous studies privative alleles were also identi ed in native breeds from Asia and South America [21,26,28]. In addition, some alleles detected in Creole cattle have also been detected in African breeds (Boran, N´Dama, Ethiopian Arsi, and Gudali) and Bos indicus (Brahman).…”
Section: Discussionmentioning
confidence: 80%
“…As a result of these studies there are 144 described BoLA-DRB3 alleles for bovines, and 303 subtypes listed in the Immuno Polymorphism Database (IPD-MHC) [30,31]. In addition, previous studies [16][17][18][19][20][21][22][23][24][25][26][27] have shown an even distribution of BoLA-DRB3 polymorphisms between the major bovine types (Bos taurus and B. indicus) and breeds. This is likely as a result of various factors including breed origin, arti cial or natural selection and geographical distribution.…”
mentioning
confidence: 99%